Nursing Contributions to Ending the Global Adolescent and Young Adult HIV Pandemic. (22nd May 2021) - Guilamo-Ramos, Vincent; Flores, Dalmacio Dennis; Randolph, Schenita D.; Andjembe Etogho, Elvine Belinda
Abstract: The welfare of adolescents and young adults (AYA) is pivotal for a sustainable future. However, despite worldwide efforts, alarming disparities in HIV morbidity and mortality persist: AYA are disproportionately affected. Specific world regions and key populations particularly warrant increased efforts to improve prevention and treatment via the global 95-95-95 strategy. Although the idiosyncrasies of AYA represent a challenge to a global response, for the past four decades, nurses have initiated and contributed to advances in HIV policy, practice, and research with AYA. Their unique position within the health care system renders success of these initiatives contingent on the collective capacity to leverage the well-established potential of nursing care. In this article, we (a) characterize the global epidemiology of HIV among AYA; (b) discuss important youth-focused HIV nursing achievements and identify nurses' unique competencies compatible with adolescent and young adult needs; and (c) examine the implications for future youth-tailored HIV nursing science and practice.